A Lieb-like lattice in a covalent-organic framework and its Stoner ferromagnetism - Wei Jiang; Huaqing Huang; Feng Liu (Nature Communications, 2019)
While ferromagnetism has been observed in an sp 2 covalent-organic framework, its origin remains unclear. Here, by first-principle and tight-binding calculations, the authors identify the Lieb-lattice-like feature of the two-dimensional covalent-organic material and the Stoner mechanism responsible for its magnetic behavior.